2016
DOI: 10.1186/s13030-016-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms are associated with oxidative stress in middle-aged women: a cross-sectional study

Abstract: BackgroundOxidative stress is known to be a factor in various diseases. In this study, we investigated whether physical and psychological symptoms of menopause, cardiovascular parameters, body composition, and lifestyle factors are associated with oxidative stress in middle-aged women.MethodsThis cross-sectional study used baseline data collected in a previous study that examined the effects of a dietary supplement on a variety of health parameters in 95 women aged 40 to 60 years. Participants had been assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“… 45 While some studies have reported increased 8-OHdG levels in depression, 1 study reported lower levels. 25 , 26 This discrepancy may have resulted from differences in the biological specimens, laboratory techniques, or the time of assessment used in the studies. 27 …”
Section: Discussionmentioning
confidence: 99%
“… 45 While some studies have reported increased 8-OHdG levels in depression, 1 study reported lower levels. 25 , 26 This discrepancy may have resulted from differences in the biological specimens, laboratory techniques, or the time of assessment used in the studies. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative stress has been associated with behavioral depression in humans (3137) and animals (3842). Further, oxidative stress mitigation reduces depression severity in humans (33,4345) and in animal models (3842,46,47).…”
Section: Introductionmentioning
confidence: 99%
“…Hypomagnesia associated with estrogen deficiency and periodontal inflammation could cause reactive oxidative stress (ROS) accumulation that manifests itself in depressive syndrome. 22 Hirose et al 9 argue that the depressive symptoms of middle-aged women is related to mood disorders and oxidative stress. In conclusion, the DPD and mineral level in GCF could be used as disorder indicators in menopausal women with periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…1 Thereafter, the main groups were divided into three sub-groups based on their menopausal phase: premenopausal (regular menstrual cycles in the past 3 months) or <50 years old (n=26), perimenopausal (experienced a menstrual period within the past 12 months but a missed period or irregular cycles during the past 3 months) or 50-55 years old (n=40), postmenopausal (no menstrual period during the previous 12 months) or >55 years old (n=18). 9,10 GCF was collected between 08.00 and 13.00 because levels of DPD peak during the morning hours. GCF was taken from the buccal site of the posterior tooth infected with gingivitis or periodontitis.…”
Section: Methodsmentioning
confidence: 99%